2014
DOI: 10.1063/1.4898665
|View full text |Cite
|
Sign up to set email alerts
|

Vibronic-structure tracking: A shortcut for vibrationally resolved UV/Vis-spectra calculations

Abstract: The vibrational coarse structure and the band shapes of electronic absorption spectra are often dominated by just a few molecular vibrations. By contrast, the simulation of the vibronic structure even in the simplest theoretical models usually requires the calculation of the entire set of normal modes of vibration. Here, we exploit the idea of the mode-tracking protocol [M. Reiher and J. Neugebauer, J. Chem. Phys. 118, 1634 (2003)] in order to directly target and selectively calculate those normal modes which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 64 publications
(79 reference statements)
0
14
0
Order By: Relevance
“…These were all paired with an Ahlrichs def2 family triple- ξ basis set (def2-TZVP). 4445 With the exception of PBE0, all functionals produced satisfactory results when compared to experimental data (Figure S3). However, in the region of interest, experimental features were best reproduced using the CAM-B3LYP range-separated functional.…”
Section: Resultsmentioning
confidence: 79%
“…These were all paired with an Ahlrichs def2 family triple- ξ basis set (def2-TZVP). 4445 With the exception of PBE0, all functionals produced satisfactory results when compared to experimental data (Figure S3). However, in the region of interest, experimental features were best reproduced using the CAM-B3LYP range-separated functional.…”
Section: Resultsmentioning
confidence: 79%
“…In the computational analysis of UV/Vis photoabsorption spectra of molecules, several authors have noticed that the band maximum E max i and the vertical excitation E v i of band i, computed at the same electronic structure level, are shifted by up to 0.2 eV, with the band maximum systematically redshifted [1][2][3][4][5]. This shift δ i (Fig.…”
Section: Introductionmentioning
confidence: 93%
“…In the last years, diverse methods for first-principle spectrum simulations have been proposed [5][6][7][8][9][10], leading to high accurate predictions of band shapes, including their vibrational resolution [11]. Through simulations of vibrationally resolved absorption spectra of several molecules, Avila Ferrer et al [3] confirmed the existence of the redshift and suggested to compare vertical excitations not to the band maximum but to the first moment M 1 (center of gravity) of the absorption band.…”
Section: Introductionmentioning
confidence: 99%
“…We do not intend to provide an exhaustive list of the works considering only one or two compounds and their comparison with experiment, or a specific chemical family of compounds. For the second category, the interested reader can find several works devoted to, e. g., fluoroborate derivatives, biological chromophores, DNA bases, cyanines, coumarins, as well as many other works focussed on band shapes rather than E0-0 energies …”
Section: Introductionmentioning
confidence: 99%